(untitled) (Bangladesh Veterinarian, 2017)
A real-time reverse transcription - polymerase chain reaction (rRT-PCR) was used for the detection of Newcastle disease virus (NDV) of poultry. A panel of seven known isolates of NDV in the form of allantoic fluid, obtained from a laboratory repository, was used for the development of the test. RNA was extracted from the allantoic fluid with a magnetic processor based automated RNA extraction system. The identity of the reference virus was first reconfirmed by a conventional RT-PCR specific for the Fusion (F) protein gene. Using these RNA, the rRT-PCR protocol was optimized with regard to the reaction mix and thermal profile using published primers and probes specific for M gene. The sensitivity of standardized rRT-PCR was compared to that of the conventional RT-PCR using serial 10-fold dilutions of the RNA of a selected sample. The thermal profile was modified from the published one; the annealing and extension steps were combined to a single step performed at 60ºC. The adopted rRT-PCR successfully amplified M gene from all the seven reference samples with a CT value ranging from 15.28 to 32.68. The rRT-PCR for M gene was 100-fold more sensitive than the conventional RT-PCR for F gene. This is the first report of the use of rRT-PCR for the detection of NDV in Bangladesh. This test will be useful for virological surveillance, particularly for screening NDV in respiratory infections. Bangl. vet. 2016. Vol. 33, No. 1, 16-22